2020
DOI: 10.1186/s12951-020-0577-9
|View full text |Cite
|
Sign up to set email alerts
|

Early-stage cervical cancer diagnosis based on an ultra-sensitive electrochemical DNA nanobiosensor for HPV-18 detection in real samples

Abstract: Background In several years ago, infection with human papillomaviruses (HPVs), have been prevalent in the worlds especially HPV type 18, can lead to cervical cancer. Therefore, rapid, accurate, and early diagnosis of HPV for successful treatment is essential. The present study describes the development of a selective and sensitive electrochemical biosensor base on DNA, for early detection of HPV-18. For this purpose, a nanocomposite of reduced graphene oxide (rGO) and multiwalled carbon nanotub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 49 publications
3
44
0
Order By: Relevance
“…A recent study suggested the feasibility of using nanotechnology to detect HPV DNA. This could be an experimental diagnostic tool in the future [ 182 , 183 ].…”
Section: Hpv Screeningmentioning
confidence: 99%
“…A recent study suggested the feasibility of using nanotechnology to detect HPV DNA. This could be an experimental diagnostic tool in the future [ 182 , 183 ].…”
Section: Hpv Screeningmentioning
confidence: 99%
“…In order to make the surface of the SPCE as homogenous as possible, it is important that they are pre-treated. These pre-treatments remove any binder residues left on the carbon surface after the curing process [ 26 , 27 , 28 , 29 ], with well-established electrochemical oxidative pre-treatments not only showing removal of binder residues left on the surface of SPCE after curing but also improvement of carbon surface sensitivity [ 30 ]. In this study, two common buffers are compared for pre-treatment: NaOH and NaCl.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, a dendritic polymer probe-amplified electrochemiluminescence (ECL) [40][41][42] scan imaging system was constructed to realize trace analysis of viral emerging infectious disease (Figure 1). Dendritic polymer probe was employed as the efficient signal giving-out component that could generate amplified ECL signal on the integrated chip.…”
Section: Introductionmentioning
confidence: 99%